Alkenone sea surface temperature from the Chiba Composition Section - Hiroto Kajita; Yusuke Suganuma; Yuki Haneda; Makoto Okada; Masanobu Yamamoto; Osamu Seki; Naohiko Ohkouchi (PANGAEA, 2024)
This study displays the high-time resolution of paleo-sea surface temperature (SST) covering the marine isotope stage (MIS) 19 based on the unsaturation ratio of long-chain alkenones (UK extquotesingle37) retrieved from the Chiba Composition Section (CbCS), central Japan. The CbCS consists of five sections: the Yoro River (35°17.41N; 140°08.48E), Yoro-Tabuchi (35°17.41N; 140°08.49E) and Urajiro (35°16.85N; 140°07.47E) sections. A total of 149 samples were processed for biomarker analyses from the Yoro-Tabuchi (ID: TB2-xx), Yoro River (ID: YT-xxx and TB-xxx), and Urajiro (ID: YW-xxx) sections of the CbCS. Please see Haneda et al. (2020, doi:10.1016/j.epsl.2019.115936) for the sample stratigraphy. After the surface was cleaned ultrasonically with ethanol, it was freeze-dried and ground into a fine powder. The powdered sediment (6-7 g) was extracted via ultrasonication with dichloromethane, dichloromethane/methanol (1:1, v/v), and methanol. The combined supernatant was dried under N2 gas and extracted with n-hexane from distilled water to obtain the neutral components. The extracted lipids were separated into four subfractions via silica gel column chromatography. The hydrocarbon fraction was eluted with n-hexane/dichloromethane (95:5, v/v). Then, the ketone fraction was eluted with n-hexane/dichloromethane (1:4, v/v) for alkenone analysis. Then, the ketones extquotesingle fraction was introduced into a gas chromatograph with a mass-selective detector and a flame ionization detector (model 7890A, Agilent Technology) equipped with a VF-5ms fused silica capillary column (30 m exttimes 0.25 mm internal diameter with 0.25 μm film, Agilent Technology). The oven temperature was programmed as follows: maintained at 40 °C for 2 min, raised to 120 °C at 30 °C/min, raised to 300 °C at 6 °C/min, and maintained at 300 °C for 20 min. Alkenone unsaturation ratios (UK extquotesingle37) were converted into SSTs (?) using the following calibration. SST = (UK extquotesingle37 - 0.039)/0.034